Digitalization of gold pawn services as an inclusive financial innovation strategy - Alda Fildza Amima; Ahmad Wildan Raikhana; Rafidah Rizky Nasution (EcoProfit: Sustainable and Environment Business, 2026)
Background: The rapid development of digital finance has fundamentally transformed the delivery of financial services and opened new opportunities for expanding financial inclusion while contributing to sustainable business transformation. In Indonesia, gold pawn (rahn) services play a strategic role as a microfinance instrument for unbanked and underbanked communities. However, existing studies on gold pawn services largely focus on operational efficiency and regulatory compliance, with limited attention to digitalization as an inclusive financial innovation strategy. Methods: This study employs a qualitative descriptive approach using a literature review method. Data were collected from national and international academic journals, regulatory documents issued by the Financial Services Authority (Otoritas Jasa Keuangan, OJK) and Bank Indonesia, and institutional publications related to digital finance, gold pawn services, microfinance, and financial inclusion. The analysis was conducted through thematic identification, conceptual categorization, and critical narrative analysis. Findings: The findings indicate that the digitalization of gold pawn services represents an institutional transformation rather than a mere technological upgrade. Digital platforms have enhanced access to microfinance by reducing geographical and administrative barriers, improving transaction efficiency, increasing transparency, and expanding service reach to micro-enterprises and younger digital-oriented users, while simultaneously reducing the environmental footprint associated with paper-based and branch-dependent pawn transactions. Nevertheless, several challenges persist, including digital literacy gaps, data security risks, public trust issues, regulatory readiness, and the risk of digital exclusion. Conclusion: Digitalization of gold pawn services has significant potential as an inclusive financial innovation strategy, provided that it is embedded within a comprehensive institutional framework that prioritizes accessibility, consumer protection, environmental efficiency, and governance. Novelty/Originality of this article: This study contributes to the literature by positioning digitalization of gold pawn services as a strategic instrument for sustainable financial inclusion, offering an institutional and inclusive perspective aligned with green microfinance transformation that goes beyond efficiency-oriented approaches.